2023
DOI: 10.3390/ijerph20032440
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Obesity and Overweight with Executive Functions in Community-Dwelling Older Women

Abstract: Among the risk factors reported for cognitive decline, the literature highlights changes in body composition. Thus, the aim of the present study was to examine the relationship between obesity/overweight and executive functions in cognitively normal older adult women. This cross-sectional study included 224 individuals (60–80 years), stratified into normal weight (n = 45), overweight (n = 98), and obesity (n = 81). As outcomes, body mass index (BMI), waist circumference (WC), and Trail Making Test Parts A and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Independent of fitness and activity levels, body composition, particularly body fatness, has also been hypothesized to contribute to changes in brain volume and cognitive function. For example, higher BMI has been associated with decreased gray matter volume across multiple brain regions (14), and links between central adiposity, as measured by waist circumference, and executive function have been observed both in children (15) and older women (16). Recent systematic reviews of cross-sectional studies have indicated that obesity, particularly central obesity, is commonly correlated with reduced cortical thickness and gray matter volume (17) and with cognitive impairment in older adults (18).…”
mentioning
confidence: 99%
“…Independent of fitness and activity levels, body composition, particularly body fatness, has also been hypothesized to contribute to changes in brain volume and cognitive function. For example, higher BMI has been associated with decreased gray matter volume across multiple brain regions (14), and links between central adiposity, as measured by waist circumference, and executive function have been observed both in children (15) and older women (16). Recent systematic reviews of cross-sectional studies have indicated that obesity, particularly central obesity, is commonly correlated with reduced cortical thickness and gray matter volume (17) and with cognitive impairment in older adults (18).…”
mentioning
confidence: 99%